Modelling of Human Behaviour and Response to the Spread of Infectious Diseases - Phang, Piau (Curtin University, 2016)
We incorporate two types of human behavioural changes into the epidemic models. First, a two-subpopulation imitation dynamic model is constructed via the replicator dynamical equations to study the self-initiated pre-cautionary health protective behaviour under the cost-benefit considerations and group pressure. Second, the impacts of additional characteristics of imperfect vaccine and the asymmetric property of smoothed best response on the vaccination behaviour are studied within the vaccination population game framework, and via the Gompertz function, respectively.